FORMULASI TABLET KUNYAH EKSTRAK ETANOL DAUN SAMBILOTO (Andrographis paniculum Ness) DENGAN VARIASI PENGISI MANITOL-DEKSTROSA - ., Sahat Pardamean Simbolon (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
meant to chew chewable tablets provide a residue with a bad taste in the mouth easily swallowed and does not leave a bad taste . Contains bitter compounds and alkaloids andrografolid which are compounds that most there are also compounds deoksiandrografolid , neoandrografolid , and more. In this formulation of mannitol used three variations : dextrose ( 80 : 20 ) , mannitol : dextrose ( 50:50 ) and mannitol : dextrose ( 20:80 ) with mannitol control : lactose ( 80:20 ) . This makes chewable tablets by wet granulation method , and tests performed that evaluation pengentapan all formulations that meet the requirements pengetapan % < 20 % produce good flow properties . Angle breaks evaluations also meet the requirements of the angle of repose formed for all formulations of < 30 Â° . Evaluation of grain particle size evenly all formulations . Tablet hardness test all meet the requirements of a chewable tablet hardness was 4-7 kPa . On the tablet friability test also meets the requirements of not more than 4 % . Tablet weight uniformity test also meets the requirement that there should not be two more tablets deviated from column A and do not deviate from column B. test the uniformity of the size of the tablet is also appropriate , disintegration time test also meets the requirement that destroyed chewable tablets should not be more than 30 minutes . And the taste test response formula 1 formula that has the highest average value compared with formula 2 and 3 because it has a larger amount of mannitol mannitol delicious taste in the mouth due .